Magnetic Resonance Spectroscopy for Evaluating the Effect of Pulsed Electromagnetic Fields on Marrow Adiposity in Postmenopausal Women With Osteopenia. Issue 5 (September 2018) - Li, Shaojun; Jiang, Hongning; Wang, Bo; Gu, Mingjun; Bi, Xia; Yin, Ying; Wang, Yu
Abstract : Objective: Pulsed electromagnetic fields (PEMFs) could promote osteogenic differentiation and suppress adipogenic differentiation in bone mesenchymal stem cells ex vivo. However, data on the effect of PEMF on marrow adiposity in humans remain elusive. We aimed to determine the in vivo effect of PEMF on marrow adiposity in postmenopausal women using magnetic resonance spectroscopy. Methods: Sixty-one postmenopausal women with osteopenia, aged 53 to 85 years, were randomly assigned to receive either PEMF treatment or placebo. The session was performed 3 times per week for 6 months. All women received adequate dietary calcium and vitamin D. Bone mineral density (BMD) by dual-energy x-ray absorptiometry, vertebral marrow fat content by magnetic resonance spectroscopy, and serum biomarkers were evaluated before and after 6 months of treatment. Results: A total of 27 (87.1%) and 25 (83.3%) women completed the treatment schedule in the PEMF and placebo groups, respectively. After the 6-month treatment, lumbar spine and hip BMD increased by 1.46% to 2.04%, serum bone-specific alkaline phosphatase increased by 3.23%, and C-terminal telopeptides of type 1 collagen decreased by 9.12% in the PEMF group ( P < 0.05), whereas the mean percentage changes in BMD and serum biomarkers were not significant in the placebo group. Pulsed electromagnetic field treatment significantly reduced marrow fat fraction by 4.81%. The treatment difference between the 2 groups was −4.43% (95% confidence interval, −3.70% to −5.65%; P = 0.009). Conclusions: Pulsed electromagnetic field is an effective physiotherapy in postmenopausal women, and this effect may, at least in part, regulate the amount of fat within the bone marrow. Magnetic resonance spectroscopy may serve as a complementary imaging biomarker for monitoring response to therapy in osteoporosis.